The role of maternal prenatal thyroid function on offspring depression: Findings from the ALSPAC cohort - Fetene, D.; Betts, K.; Alati, Rosa (Cambridge University Press, 2019)
© Cambridge University Press 2019. Maternal thyroid dysfunction during pregnancy may contribute to offspring neurobehavioral disorders. In this paper, we investigate the relationship between maternal thyroid function during pregnancy and offspring depression and anxiety. Data were taken from the Avon Longitudinal Study of Parents and Children. A total of 2,920 mother-child pairs were included. Thyroid-stimulating hormone levels, free thyroxine (FT4), and thyroid peroxidase antibodies were assessed during the first trimester of pregnancy because maternal supply is the only source of thyroid hormone for the fetus during the first 12 weeks of gestation. Child symptoms of depression and anxiety were assessed using the Development and Well-Being Assessment at ages 7.5 and 15 years. The odds of presenting with depression and anxiety were estimated using the generalized estimating equation. The level of FT4 during the first trimester of pregnancy was associated with child depression combined at ages 7.5 and 15 (odds ratio = 1.21, 95% confidence interval [1.00, 1.14]. An increase of 1 standard deviation of FT4 during pregnancy increased the odds of child depression by 28% after adjustment made for potential confounders. No association was found among maternal levels of thyroid-stimulating hormone, FT4, and thyroid peroxidase antibodies and childhood anxiety. In conclusion, increased levels of FT4 during the first trimester of pregnancy appear be linked to greater risk of offspring depression.